The Theme of Inequality in F.M. Dostoevsky’s Story Netochka Nezvanova - Nadezhda G. Shervarly (Russian Academy of Sciences. A.M. Gorky Institute of World Literature, 2019)
In the article we examine the topic of inequality Dostoevsky’s novel Netochka Nezvanova. The equation of “rovnya-nerovnya” throughout the work manifests itself in different ways: both in material terms and in the spiritual. Netochka calls Efimova “rovney” (equal, peer) to herself, develops relations with Katya to equality. Efimov considers other musicians unworthy of himself, that is “nerovnya” (not equal). The relations of Alexandra Mikhailovna and Peter Alexandrovich are also based on the idea of inequality. Finally, a letter to S.O., in which he calls himself “nerovnya” to Alexandra Mikhailovna. While comparing all these aspects, the ambiguous understanding the word “nerovnya” has for different people is revealed. Those who consider themselves “nerovnya” to someone are, in fact, higher than others. The article also considers the difference between inequality of the spirit and inequality of the soul, which can help us understand about what inequality S.O. writes in his letter.